Implementasi Peraturan Pemerintah Nomor 94 Tahun 2021 di Kantor Pengadilan Negeri Tondano - Gabriella Mewengkang; Devie S. R. Siwij; Laurens Bulo; Ressy Mewengkang (CV. Kurnia Grup, 2026)
This paper aimed to examine how Government Regulation No. 94 of 2021 on Civil Servant Discipline has been put into practice at the Tondano District Court Class IB, focusing on attendance filling mechanism, punctuality, dispensation, and evaluation. A qualitative descriptive design was employed, gathering evidence through participatory observation, in- depth interviews, and document review, analyzed using the interactive model of Miles, Huberman, and Saldana. Findings show that the court operates a digital attendance system through the SIKEP application with facial recognition and location verification, though recurring server disruptions remain a practical obstacle. Most employees observe punctuality requirements, while a minority face delays due to commuting distance, weather, and limited transport. Dispensation procedures run adequately through supervisory communication and the digital platform, and attendance evaluation is conducted daily and monthly, resulting in reprimands and a one-percent salary deduction for latecomers. The study concludes that implementation is progressing reasonably well, yet sustained effectiveness requires stronger infrastructure investment and a more developmental rather than purely punitive approach to employee discipline